Approach of Individualised Medicine in a Complicated Case of Cholelithiasis, Elongated Uterus with Ovarian Cyst—An Evidence-Based Case Report - Pandey, Swati; Pandit, Raj K. (Homœopathic Links, 2022)
Gallstones are the most common biliary pathology. They are formed because of abnormal bile composition. Symptomatic gallstones present as pain in the right upper quadrant or epigastric region, which may radiate to the back. Ultrasonography of the gallbladder is very accurate in the identification of gallstones. Laparoscopic cholecystectomy is a minimal-access approach for the removal of the gallbladder together with its stones. A 28-year-old lady presented with complaints of pain in the right upper quadrant of abdomen, which was relieved by pressure, nausea and occasionally vomiting especially after having a rich meal for 1 month with constant dull pain in lower abdomen during menses for 2 to 3 months. Her ultrasonography of whole abdomen revealed cholelithiasis (stone size 8mm), elongated uterus with left ovarian cyst. Individualised medicine Natrum muriaticum was prescribed in a centesimal scale which showed a positive effect in the case within a short span of time. Causal attribution of changes in her condition to the homoeopathic treatment was assessed by Modified Naranjo Criteria. Future observational studies and randomised control trials are suggested to ascertain the efficacy of homoeopathic medicine in such cases.
Keywords: case report; cholelithiasis; homoeopathy; individualised medicine; Natrum muriaticum; ovarian cyst